PEMBELAJARAN IPA SMP BERBASIS KETERAMPILAN PROSES SAINS DENGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - TRIWIYONO, TRIWIYONO; TANTA, TANTA; PANDA, FLORENTINA MARIA (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to improve students' understanding of the concept by applying Science Process Skill Based Learning (PBKPS) with the Discovery Learning model. The method used in this research is Research and Development using 3D models, namely Define, Design, and Develop. Define is the activity of gathering various information needed (need assessment). Design is the activity of designing an initial product or learning draft. Develop is a product developing activity. At the trial design phase that is used is One Group Pretest-Posttest Design. The population used in this study was Jayapura VII Class VIII SMP Negeri 2 totaling 280 people. The sampling technique is done by using purposive technique and cluster sampling. The number of samples in this study were 30 people. The results showed that: 1) Science Process Skills-based learning (KPS) can be implemented well by the teacher, and 2) the acquisition of N-gain understanding of the concept of the limited trial results is classified as moderate.